Nonergodic property of the space–time coupled CTRW: Dependence on the long-tailed property and correlation - Liu, Jian; Li, B.; Chen, X. (Elsevier BV * North-Holland, 2018)
© 2017 Elsevier B.V. The space–time coupled continuous time random walk model is a stochastic framework of anomalous diffusion with many applications in physics, geology and biology. In this manuscript the time averaged mean squared displacement and nonergodic property of a space–time coupled continuous time random walk model is studied, which is a prototype of the coupled continuous time random walk presented and researched intensively with various methods. The results in the present manuscript show that the time averaged mean squared displacements increase linearly with lag time which means ergodicity breaking occurs, besides, we find that the diffusion coefficient is intrinsically random which shows both aging and enhancement, the analysis indicates that the either aging or enhancement phenomena are determined by the competition between the correlation exponent ? and the waiting time's long-tailed index a.